Pengaruh Social Marketing Campaign dan Kepekaan Sosial terhadap Jumlah Donatur ZIS di saat Pandemi (Studi Kasus LAZ Harfa Banten) - Anton Purwanto; Oom Mukarromah; Sulaeman Jajuli (PROGRAM STUDI EKONOMI ISLAM PROGRAM PASCASARJANA IAIN SULTAN MAULANA HASANUDDIN BANTEN, 2022)
This study aims to determine whether social marketing campaigns and social sensitivity have a simultaneous and partial effect on the number of donors of Zakat, Infak, and Alms (ZIS) during the Covid-19 pandemic at the Amil Zakat Institution of Harapan Dhuafa Banten. The method is descriptive quantitative using a questionnaire with a Likert scale. The object of this research is LAZ Harapan Dhuafa Banten, where the sample taken is 30 respondents from the amil staff of LAZ Harfa Banten in the period November 2021. The data analysis method used in this study is a prerequisite test (classical assumption test). multiple regression analysis, F test and T test with the help of SPSS version 26.0 application program to prove each hypothesis of this research. The test results in this study indicate that: (1) partially the Social Marketing Campaign (X1) variable does not have a negative and insignificant effect on the Number of Donors of ZIS (Y), where tcount < ttable i.e. 1.638 < 1.701. (2) partially the Social Sensitivity variable (X2) has a significant or positive effect on the number of ZIS donors (Y), where tcount > ttable is 2,688 > 1,701. (3) Simultaneously the variables of Social Marketing Campaign (X1) and Social Sensitivity (X2) have a positive and significant effect on the Number of Donors of ZIS (Y), where Fcount > Ftable (15,068 > 3,34). Thus, these two variables can be factors that affect the number of ZIS donors at LAZ Harfa Banten during a pandemic.